Restoring the Meratus: a permaculture-based nexus supporting adaptive practice in indigenous communities - Muhamat, Muhamat; Utari, Nofi; Anitasari, Lucia Desti; Maulidiyah, Hikmah; Krisdianto, Krisdianto (Agriekonomika, 2026)
This study investigates the role of permaculture-based agroforestry in strengthening ecosystem restoration, food security, and community resilience within the indigenous Dayak Meratus population in South Kalimantan, Indonesia. Following a major flash flood in 2021, an integrated landscape management initiative was implemented in Hinas Kiri village. From January to June 2025, data from 100 respondents collected through modified snowball sampling revealed measurable improvements in ecological and socio-economic indicators. The implementation of agroforestry systems based on permaculture principles resulted in increased plant diversity, improved soil conditions, and positive trends in tree growth Biophysical assessments showed increased tree canopy cover and trunk diameter (5.7–7.1%) across Shorea sp., Peronema canescens, and Hevea brasiliensis, while crop yields rose for banana (+8.0%), taro (+8.9%), and rattan (+12.5%). Grounded theory analysis indicated a perceptual shift among farmers, who increasingly viewed permaculture as a climate adaptation strategy and pathway to economic diversification. A digital monitoring prototype and preliminary policy brief were developed to support adaptive management and evidence-based decision-making. The findings provide empirically grounded insights and demonstrate the value of an integrative nexus-based approach for climate-resilient landscape governance in rural area.